Limit functionals for a semicontinuous difference of renewal processes with discrete time - Yezhov, I. I.; Kadankov, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For a difference, semicontinuous in discrete topology, of two renewal processes with discrete time, the distribution of principal limit functionals is found.